Analysis of the Influence of Accounting Liquidity on Business Combinations PT Indosat Tbk - Rani Fitria; Rara Ivanka; Della Chastika; Putri Melani; Wiwik Apriani; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
The purpose of this study is to compare the financial liquidity performance of PT. Indosat Tbk before and after the business combination in 2020-2023 with Hutchison 3 Indonesia. This study combines a quantitative descriptive research approach with secondary data from the Indonesia Stock Exchange. Based on the results of the analysis, it shows that there are differences in liquidity ratios, namely the Current Ratio, Quick Ratio, and Cash Ratio between the period before the business combination in 2020-2021 and the year after the business combination. 2022-2023 which shows an increase and also a decrease where in 2020 the current ratio value was 42.35 then in 2021 it decreased to 40.13% and increased after the combination was carried out in 2022 by 52.08% but decreased again in 2023 by 45.35%. This shows that the company is still facing liquidity constraints, especially in its ability to cover all of its short-term obligations.